Patterns and Evaluation of Prescription Writing in Psychiatric Clinics - Salman, Saad; Ismail, Muhammad; Awan, Naila Riaz; Anees, Muhammad (Journal of Postgraduate Medical Institute, 2013)
Objectives: The purpose of this study was to screen drug prescriptions of Psychiatrist in Peshawar area of Pakistan for the essential elements of prescriptions and to investigate the prescribing trends at Peshawar. Methodology: This observational study was carried out at LRH Peshawar on 602 prescriptionsin 5 months duration. The prescriptions were collected from the patients admitted to LRH and the variables were checked and noted directly into electronic form. Results: Averagely 3.34 drugs were prescribed per prescription, in which drug-related variables: (i)strength of medication was indicated for all drugs in 409 (67.94%) of the prescriptions and were missingfor some drugs in 177 (29.4%) prescriptions, (ii) total quantity of a drug to be dispensed was indicatedfor any drug in just over 111(18.43%) of prescriptions, (iii) The instructions for taking the medication werecomplete in only 301 (50%) of prescriptions. Fluoxetine alone or in combination (8.4%) was the mostcommonly prescribed antidepressant. There were 319 (15.8%) non-steroidal anti-inflammatory drugs(NSAIDs) and/or analgesics. Vitamin preparations accounted for 4.02% of all drugs dispensed. Conclusion: SSRI's were the most frequently prescribed medication in majority of prescriptions. Inconsistencyregarding different prescription components was observed, such as strength of medication, frequencyor instruction for medication use etc.